MATHEMATICS TEACHER’S ENGAGEMENT AND STUDENTS’ MOTIVATION TO LEARN MATHEMATICS - Mary Juliet Adapon Doño; Benjamin Baguio Mangila (Jurnal Infinity, 2021)
Effective teachers are those who are highly engaged and who have an essential role in promoting student motivation and achievement. Thus, this study was conducted to ascertain the engagement of Mathematics teachers and its relation to the learning motivation of students in a state college in the Philippines. It employed the mixed methods, specifically Creswell’s (2014) sequential explanatory approach, with the survey-questionnaire, interview, and focus group discussion as data collection techniques. The findings of the study revealed that teacher’s engagement in Mathematics in terms of “Body Language and Behaviors,” “Consistent Focus,” and “Individual Attention,” were “Very High” while “Rigorous Thinking,” “Meaningfulness of Work,” “Verbal Participation,” “Clarity of Teaching,” “Performance Orientation,” “Interest and Enthusiasm,” and “Confidence,” were only “High.” Meanwhile, students’ motivation to learn Mathematics as to “Relevance,” “Interest,” “Satisfaction,” and “Confidence” were also “High”. The test of hypothesis on significant correlation showed that there was a close association between teacher’s engagement in Mathematics and students’ motivation to learn Mathematics. There was also a corroboration between the quantitative data obtained from the survey and the qualitative data acquired during the interview and focus group discussion. The result further implied that teacher’s high engagement contributes positively to students’ willingness to learn essential concepts and skills in Mathematics.